Hemispheric Asymmetries in Price Estimation: Do Brain Hemispheres Attribute Different Monetary Values? - Giuliani, Felice; D’Anselmo, Anita; Tommasi, Luca; Brancucci, Alfredo; Pietroni, Davide (Frontiers in Psychology, 2017)
The spatial number association of response code effect (SNARC effect) has been associated with a wide range of magnitude processing. This effect is due to an implicit relationship between numbers and horizontal space, according to which weaker magnitudes and small numbers are represented on the left, whereas stronger magnitudes and large numbers are represented on the right. However, for some particular type of magnitudes such as price, judgments may be also influenced by perceived quality and thus involving valence attribution biases driven by brain asymmetries. In the present study, a lateralized tachistoscopic presentation was used in a price estimation task, using a weight estimation task as a control, to assess differences in asymmetries between these two attributes. Results show a side bias in the former condition but not in the latter, thus indicating that other non-numerical mechanisms are involved in price estimation. Specifically, prices were estimated lower in the left visual field than in the right visual field. The proposed explanation is that price appraisal might involve a valence attribution mechanism leading to a better perceived quality (related to higher prices) when objects are processed primarily in the left hemisphere, and to a lower perceived quality (related to lower prices) when objects are processed primarily in the right hemisphere.